Age, Body Mass, Usage of Exogenous Estrogen, and Lifestyle Factors in Relation to Circulating Sex Hormone–Binding Globulin Concentrations in Postmenopausal Women. (1st January 2014) - Goto, Atsushi; Chen, Brian H; Song, Yiqing; Cauley, Jane; Cummings, Steven R; Farhat, Ghada N; Gunter, Marc; Van Horn, Linda; Howard, Barbara V; Jackson, Rebecca; Lee, Jennifer; Rexrode, Kathryn M; et al.
Abstract: BACKGROUND: Circulating concentrations of sex hormone–binding globulin (SHBG) have been associated with cardiovascular diseases, type 2 diabetes, metabolic syndrome, and hormone-dependent cancers; however, correlates of SHBG concentrations are not well understood. METHODS: We comprehensively investigated correlates of SHBG concentrations among 13 547 women who participated in the Women's Health Initiative and who had SHBG measurements. We estimated study- and ethnicity-specific associations of age, reproductive history, usage of exogenous estrogen, body mass index (BMI), and lifestyle factors such as physical activity, smoking, alcohol consumption, coffee intake, and dietary factors with SHBG concentrations. These estimates were pooled using random-effects models. We also examined potential nonlinear associations using spline analyses. RESULTS: There was no significant ethnic difference in the age-adjusted mean concentrations of SHBG. Age, exogenous estrogen use, physical activity, and regular coffee intake were positively associated with SHBG concentrations, whereas BMI was inversely associated with SHBG concentrations after adjustment for potential confounding factors. Similar patterns were observed among both ever users and never users of exogenous estrogen. The spline analysis indicated nonlinear relations of regular intake of coffee, age, and BMI with SHBG concentrations. Two or more cups/day of regular coffee consumption and age of 60 years or older were associated with higher SHBG concentrations; the inverse BMI–SHBG relation was especially strong among women whose BMI was below 30. CONCLUSIONS: In this large sample of postmenopausal women, age, exogenous estrogen use, physical activity, regular coffee intake, and BMI were significant correlates of SHBG concentrations, presenting potential targets for interventions.